Tenderness, histomorphology of muscle fiber and gene expression in primal cuts of cattle-A Review - Sarker, T; Jahan, R; Deen , RA; Ghosh, D; Hashem, MA (Meat Research, 2024)
This review focuses on the relationship between tenderness, the structure of muscle fibers (histomorphology) and gene expression in the primal cuts of beef with an emphasis on understanding how these factors contribute to meat quality. This review describes the biochemical and molecular findings in connection with this proteolytic system and their relation with meat tenderness in bovine. The findings of DNA polymorphisms and mRNA and protein expression are described as tools to predict meat tenderness. Tenderness, a key determinant of consumer satisfaction, is influenced by the structural and biochemical properties of muscle fibers, which vary across different primal cuts. The paper synthesizes existing literature on the morphological characteristics of muscle fibers, including fiber type, size, and distribution, and their relationship to meat tenderness. Additionally, it explores the role of gene expression in muscle development and postmortem changes which further impact meat texture and quality. The review discusses key research findings on how genes control muscle growth, the breakdown of proteins, and the structure of muscle fibers, all of which play a role in tenderness. It highlights areas where more research is needed, especially regarding how genes (Calpain, Myostatin, Calpastatin) and muscle structure work together to affect tenderness. Finally, this paper suggests future research directions aimed at improving meat quality through a better understanding of the genetic and structural basis of tenderness in cattle. Research on the molecular basis of meat tenderization may be fruitful particularly to the meat industry and may allow amendment of handling practices of preslaughter andpostmortem treatments that improves meat quality.